Teknologi Manajemen Hubungan Pelanggan : Menjembatani Kesenjangan Antara Pendidikan dan Praktik Pemasaran - Septi Handayani; Farhan Hermawan; Regina Angelina; Wenny Chandra Mandagie (PT. Cendekia Sapta Indonesia, 2022)
This article aims to test and analyze Customer Relationship Management Technologies that Bridge the Gap Between Education and Marketing Practices. The sample used in this article is Employees and Business Actors. The amount of data in this study were 70 respondents and collected by purposive sampling method. The test was carried out using the Structural Equation Model (SEM) method. The independent variables in this article are CRM Knowledge, Frequency of CRM use, Marketing Practices The dependent variable is CRM. The results of this study are (1) Knowledge of CRM system features has a positive effect on CRM use (2) Knowledge of CRM system features does not have a positive effect on sales (3) The frequency of CRM use has a positive effect on sales.